Decreased Mechanical Work Demand in the Chopart Joint After Total Ankle Replacement. (October 2022) - Deleu, Paul-André; Naaim, Alexandre; Chèze, Laurence; Dumas, Raphaël; Devos Bevernage, Bernhard; Birch, Ivan; Besse, Jean-Luc; Leemrijse, Thibaut
Background: The success of total ankle replacement (TAR) must be based on restoring reasonable mechanical balance with anatomical structures that can produce mechanical joint work through elastic (eg, tendons, fascia) or viscoelastic (eg, heel pad) mechanisms, or by active muscle contractions. Yet, quantifying the work distribution across the affected joint and the neighboring foot joints after TAR is lacking. Therefore, the objective of this study was to investigate if there is a change in the joint work distribution across the Ankle, Chopart, Lisfranc and Metatarsophalangeal joints during level walking before and after patients undergo TAR. Methods: Fifteen patients with end-stage ankle osteoarthritis scheduled for primary TAR for pain relief were recruited and peer-matched with a sample of 15 control subjects. All patients underwent a 3D gait analysis before and after surgery, during which a kinetic multisegment foot model was used to quantify intersegmental joint work. Results: The contribution of the Ankle joint ( P = .007) to the total foot and ankle positive work increased significantly after TAR. In contrast, a significant decrease in the contribution to the total foot and ankle joint positive work ( P < .001) were found at the Chopart joint after TAR. The foot joints combined produced a significant increase in a net mechanical work from +0.01 J/kg before surgery to +0.05 J/kg after TAR ( P = .006). Conclusion: The findings of this study corroborate the theoretical rationale that TAR reduces significantly the compensatory strategy in the Chopart joint in patients with end-stage ankle osteoarthritis after TAR. However, the findings also showed that the contribution of the ankle joint of patients after TAR to the total foot and ankle joint positive work remained impaired compared to the control group.